Pengembangan Media Pembelajaran Matematika dengan Macromedia Flash - Maskur, Ruhban; Nofrizal, Nofrizal; Syazali, Muhamad (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
This research and development aims to 1) to determine the feasibility of developing mathematics learning media using the Macromedia Flash application program, 2) to find out the attractiveness of students' responses to the development of mathematics learning media using the Macromedia Flash application program. This research was carried out using the Research and Development (R and D) method using the modified Borg and Gall development procedure, which is 10 stages, with only limited access to the 7th stage. Data collection techniques using validation questionnaire sheet. The instrument used was a validation questionnaire sheet to determine the feasibility of the module and questionnaire for student responses to find out the interest. Data analysis techniques used in research and development are quantitative descriptive to process data in the form of scores from the validator's assessment and student response, while qualitative descriptive to describe the data in the form of commentary suggestions for improvement from the validator. Based on the results of the validation of the development of mathematics learning media using the Macromedia Flash application program an average score was obtained; (1) the feasibility of developing mathematics learning media using macromedia flash application program results of the validation of material experts obtained an average of 3.73, on linguistic aspects obtained an average of 3.64, on the aspect of feasibility evaluation obtained an average of 3.66, on media experts obtained on average (aspects of media efficiency obtained an average of 3.87, aspects of the function of the buttons obtained an average of 3.5 and the Graphical aspect obtained an average score of 3.4). (2) attracting the development of mathematics learning media using the macromedia flash application program students' responses obtained an average score of 3.61 in the